Targeting NANOS1 in triple-negative breast cancer: synergistic effects of digoxin and PD-1 inhibitors in modulating the tumor immune microenvironment - Wang, Tangyi; Lei, Yadian; Sun, Jingwei; Wang, Li; Lin, Yuxin; Wu, Zhijing; Zhang, Shoude; Cao, Chengzhu; Wang, Haiyan (Frontiers in Oncology, 2025)
IntroductionTriple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer resistant to endocrine and targeted therapies. Immune checkpoint inhibitors (ICIs) have shown significant efficacy in various cancers. Taraxacum officinale, commonly known as dandelion, has traditionally been used to treat breast-related diseases and is recognized for its beneficial composition and low side effects. FDA-approved drugs, having undergone rigorous validation for their safety, efficacy, and quality, provide a foundation for drug repurposing research. Researchers may explore FDA-approved drugs targeting the potential target NANOS1 for TOE (Taraxacum officinale extract) treatment to develop innovative therapeutic strategies. In this context, Dig (Digoxin) and AA (Algestone acetophenide) have been identified as potential drug candidates for further exploration of their therapeutic effects and application potential in targeting NANOS1.MethodsRNA sequencing (RNA-seq) was employed to identify potential targets for triple-negative breast cancer (TNBC) from TOE. Bioinformatics tools, including bc-GenExMiner v4.8, the Human Protein Atlas, and the TIMER database, were utilized for target identification. Molecular docking studies assessed FDA-approved drugs interacting with these targets, with Dig and AA selected as candidate drugs. The therapeutic efficacy of Dig and AA in combination with PD-1 inhibitors was evaluated using the 4T1 mouse model. Flow cytometry was applied to assess lymphocyte infiltration in the tumor immune microenvironment. RNA-seq analysis after target silencing by small interfering RNA (siRNA) was performed, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. Validation of findings was conducted through quantitative PCR and Western blot analysis.ResultsTOE inhibited TNBC cell growth, migration, and invasion, as assessed by CCK-8 and transwell assays. RNA-seq indicated the effects may be due to NANOS1 down-regulation. Survival analysis showed lower NANOS1 expression correlated with better prognosis. Immunoinfiltration analysis indicated a negative correlation between NANOS1 levels and activated NK cells. Molecular docking identified Dig and AA as high-affinity binders of NANOS1. Animal experiments showed Dig and PD-1 inhibitor combination enhanced immunotherapy efficacy for TNBC.DiscussionThe findings from this study suggest that TOE may offer a novel therapeutic approach for TNBC by targeting NANOS1, a protein whose down-regulation is associated with improved patient outcomes. The negative correlation between NANOS1 and activated NK cells highlights the potential role of the immune system in TNBC pathogenesis and response to treatment. The identification of Dig as potential drugs targeting NANOS1 provides a new direction for drug repurposing in TNBC. The synergistic effect of Dig and PD-1 inhibition observed in animal models is promising and warrants further investigation into the role of immunotherapy in TNBC treatment. Overall, this study identifies NANOS1 as a new target for TNBC therapy and suggests a combination therapy approach that could enhance immunotherapy effectiveness and improve patient outcomes.